Mnt modulates Myc-driven lymphomagenesis - Campbell, Kirsteen J (Cell Death Differ, 2017)
The transcriptional represser Mnt is a functional antagonist of the proto-oncoprotein Myc. Both Mnt and Myc utilise Max as an obligate partner for DNA binding, and Myc/Max and Mnt/Max complexes compete for occupancy at E-box DNA sequences in promoter regions. We have previously shown in transgenic mouse models that the phenotype and kinetics of onset of haemopoietic tumours varies with the level of Myc expression. We reasoned that a decrease in the level of Mnt would increase the functional level of Myc and accelerate Myc-driven tumorigenesis. We tested the impact of reduced Mnt in three models of myc transgenic mice and in p53(+/−) mice. To our surprise, mnt heterozygosity actually slowed Myc-driven tumorigenesis in vavP-MYC10 and Eμ-myc mice, suggesting that Mnt facilitates Myc-driven oncogenesis. To explore the underlying cause of the delay in tumour development, we enumerated Myc-driven cell populations in healthy young vavP-MYC10 and Eμ-myc mice, expecting that the reduced rate of leukaemogenesis in mnt heterozygous mice would be reflected in a reduced number of preleukaemic cells, due to increased apoptosis or reduced proliferation or both. However, no differences were apparent. Furthermore, when mnt(+/+) and mnt(+/−) pre-B cells from healthy young Eμ-myc mice were compared in vitro, no differences were seen in their sensitivity to apoptosis or in cell size or cell cycling. Moreover, the frequencies of apoptotic, senescent and proliferating cells were comparable in vivo in mnt(+/−) and mnt(+/+) Eμ-myc lymphomas. Thus, although mnt heterozygosity clearly slowed lymphomagenesis in vavP-MYC10 and Eμ-myc mice, the change(s) in cellular properties responsible for this effect remain to be identified.